Jawabanmu

2014-08-27T21:17:21+07:00
Jawaban paling cerdas!
2014-08-27T21:20:10+07:00
A. x + 5 = -2
   x = -2 -5
   x = -7
b. 8- (-17)= -x + 22
    8 + 17 = -x + 22
   25 = -x + 22
   25 - 22 = -x
   -x = 3
     x = -3

c. 8 + (-x) = 23
     8 - x = 23
     -x = 23 - 8
     -x = 15
     x = -15

d. 
-x - 2 = -11
     -x = -11 + 2
     -x = -9
       x = 9

e. x + 3 = 2X -2
    3 = 2x - x - 2
   3 = x - 2
   -x = -2 - 3
   -x = -5
   x = 5
yang e?
e. x + 3 = 2X -2
3 = 2x - x - 2
3 = x - 2
-x = -2 - 3
-x = -5
x = 5